Incidence and types of vascuar accesses in patients on chronic hemodialysis - Marić, Nikola B; Brković, Voin Lj (Medicinski podmladak, 2018)
Introduction: End-stage renal disease is the last stage of chronic renal disease and it is treated with renal replacement therapy. Hemodialysis (HD) represents a type of renal replacement therapy, which requires a vascular access. Types of vascular accesses are: arteriovenous fistula (AVF), arteriovenous graft (AVG) and Hickman line. If there is no vascular access, central venous catheter (CVC) can also be used. Aim: To present the incidence and types of vascular accesses for hemodialysis in patients with ESRD, as well as analyse different types of vascular accesses and their complications in regard with the clinical and demographic characteristics of the participants. Materials and methods: Study included 153 participants treated at Clinic of nephrology, Clinical Center of Serbia, during 2014 and 2015. Participants were admissioned to create vascular access prior to hemodialysis, to immediatly start hemodialysis due to uremic syndrome, and patients whose vascular access was malfunctioning. Clinical and demographic data was collected from medical records. Results: The most often created vascular access was primary AVF (68,7%), REDO AVF was created to 11,1% while Hickman line was implanted to 15%, and AVG to 3,9% patients (p